THE RELATIONSHIP OF LINGUISTICS AND LOGIC - M. O. Rahimova (International Journal of Innovations in Engineering Research and Technology, 2023)
It is known that any special science develops on the basis of philosophy, logic, methodology and methods of leading natural sciences. This article is aimed at explaining the direct relationship between language and the science of logic, and about the importance of researching language based on the categories of logic.